Diffusion, segregation and solid-state phase transformations : Course reminders and solved problems - Blavette, Didier (Current Natural Sciences, 2022)
This book contains a set of solved problems on the thermodynamics of phase transformations, diffusion and kinetics in alloys. These problems, preceded by a reminder of the course, are completed by answers detailing each stage of the calculations. The topics covered in the book (precipitation, ordering, segregation on crystalline defects, growth of a thin film, oxidation, creep, doping of semiconductors, etc.) are essential for the design of materials and the optimisation of heat treatments and properties, whether for structural materials (steels, Ni, Al, Cu, Ti-based alloys, etc.) or functional materials (semiconductors, alloys and magnetic multilayers, etc.). They often lead to an industrial problem (aeronautics, nuclear power plants, microelectronics, etc.). This book is intended for teachers and students of bachelor's and master's degrees, but also for engineering students, PhD students and researchers.